1966
DOI: 10.1085/jgp.49.5.937
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical Factors in Potentiation of Contraction by Heavy Metal Cations

Abstract: In addition to the previously studied Zn ~+, low concentrations (about 0.5 mM) of Be g+, Ba ~+, Cd 2+, Ni ~+, Cu 2+, Pt 4+, and, outstandingly, 0.5 /~ of ~+ UOa , potentiate the twitch of frog sartorius and toe muscles by prolonging the active state of contraction. The degree of potentiation is a roughly S-shaped function of p(metal2+), suggesting that each metal binds to a ligand of the muscle fiber, representative apparent affinity constants being: UO~ +, 5 X 106; Zn ~'+, 2.8 X 105; and Cd 2+, 2 X 104. UO~ +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 22 publications
5
31
0
Order By: Relevance
“…The AZ III signal was also prolonged so that T2 and T3 were 6.4 and 23 msec, whereas Tl was little changed. It was reported that Zn action potential or twitch tension developed slowly and it took 1 min for the Zn action to attain the maximum when examined for a single fiber (STANFIELD, 1973), or 7 min examined for the toe muscle (SANDOW and IsAACSON, 1966). In the present study, the muscle preparation was a single layer of a few fibers and the solution was not exchanged rapidly.…”
Section: Effects Of Twitch Potentiatorsmentioning
confidence: 77%
“…The AZ III signal was also prolonged so that T2 and T3 were 6.4 and 23 msec, whereas Tl was little changed. It was reported that Zn action potential or twitch tension developed slowly and it took 1 min for the Zn action to attain the maximum when examined for a single fiber (STANFIELD, 1973), or 7 min examined for the toe muscle (SANDOW and IsAACSON, 1966). In the present study, the muscle preparation was a single layer of a few fibers and the solution was not exchanged rapidly.…”
Section: Effects Of Twitch Potentiatorsmentioning
confidence: 77%
“…Sandow & Isaacson (1966) also reported a contractile effect of NEM. In the present experiments, however, the contractile effect was seen infrequently and was of very variable amplitude.…”
Section: Mechanical Effectsmentioning
confidence: 91%
“…Also, the shoulder which quite often appears on the falling phase of the twitch (Text- fig. 1 D, E In like manner, when a curarized whole muscle is stimulated with transverse pulses, prolonging the stimulus from 0-2 to 10 msec decreases the twitch amplitude (Kelly et al 1964;Sandow & Isaacson, 1966;Close & Hoh, 1968). But when curare is absent the force of the contraction elicited is greatly increased as the stimulus duration is prolonged (Kelly et al 1964).…”
Section: Isometric Contractionsmentioning
confidence: 94%